About three mechanisms of transformation of lowfrequency energy of oscillations to the energy of highfrequency oscillations - Buts, V.A.; Yegorov, A.M. (Вопросы атомной науки и техники, 2011)
The brief review of the most important results which have been gotten at study of the mechanism of the high numbers harmonics excitation by nonrelativistic oscillators, the mechanism of quantum whirligig effect and the mechanism of secondary resonances is given. These mechanisms give opportunity for transforming energy of low frequency oscillations to energy of high frequency oscillations.